A new method for the quantification of monosaccharides, uronic acids and oligosaccharides in partially hydrolyzed xylans by HPAEC-UV/VIS. (20th April 2016) - Lorenz, Dominic; Erasmy, Nicole; Akil, Youssef; Saake, Bodo
Highlights: Complete hydrolysis of xylan cannot be achieved without losses. Partial hydrolysis prevents degradation of monosaccharides and uronic acids. Exact quantification of oligosaccharides by labeling and HPAEC-UV/VIS. No carbohydrate standards are required for the developed method. Results of the new methods are confirmed by 13 C NMR of the original xylans. Abstract: A new method for the chemical characterization of xylans is presented, to overcome the difficulties in quantification of 4- O -methyl-α-D-glucuronic acid (meGlcA). In this regard, the hydrolysis behavior of xylans from beech and birch wood was investigated to obtain the optimum conditions for hydrolysis, using sulfuric acid. Due to varying linkage strengths and degradation, no general method for complete hydrolysis can be designed. Therefore, partial hydrolysis was applied, yielding monosaccharides and small meGlcA containing oligosaccharides. For a new method by HPAEC-UV/VIS, these samples were reductively aminated by 2-aminobenzoic acid. By quantification of monosaccharides and oligosaccharides, as well as comparison with borate-HPAEC and 13 C NMR-spectroscopy, we revealed that the concentrations meGlcA are significantly underestimated compared to conventional methods. The detected concentrations are 85.4% (beech) and 76.3% (birch) higher with the new procedure. Furthermore, the quantified concentrations of xylose were 9.3% (beech) and 6.5% (birch) higher by considering the unhydrolyzed oligosaccharides as well.